Quarter milking parameters by lactation in dairy cows - Mišeikienė, Ramutė (Array, 2019)
The study was conducted on 229 dairy cows in Lithuania. DeLaval milking robots were used for cows’ milking. Milk yield (kg), milking duration (min), milk flow (kg/min), peak flow rates (kg/min) by cow lactation in separate udder quarters were analyzed. The statistical analysis of the research data was performed using the data collection and analysis program package Statistical Package for Social Science 22 for Windows, Kolmogorov-Smirnov test and One-Factor Dispersion Analysis (ANOVA) model. Distribution of the udder quarters is very important in the cow milking process. Milk yield from cow front udder quarters was about 4.6 kg (42.2 %) and from rear udder quarters 6.32 kg (57.8 %) (P<0.05). The milk content in front quarters was significantly lower than in the rear udder quarters in all dairy cows (P<0.05). Cows of the first lactation showed lower milk production per milking in all udder quarters when compared to other lactation cows (P<0.05). The duration of milking of cows in third and more lactation in front quarters was shorter than that of the first lactation cows (P<0.005). Along the increase in the number of cows’ lactations, the milking time in the front quarters decreased. The average milk flow and the peak flow in the first lactation cows were found to be lower than that in older cows (P<0.05).